The Effect of Beans and Baking on Banana Bar Qualities - Riyanti Ekafitri; Dewi Desnilasari; Rhestu Isworo; Dian Rachmawanti Affandi; Rohmah Lutfiyanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Beans are good protein sources for producing banana bars for emergency foods. According to the previous reports, the baking temperatures and times affect the quality of the banana bar. This study aims to evaluate the effect of bean flour types (soybean, mung, and winged bean) as well as the baking temperatures and times on the banana bars chemical characteristics, organoleptic, and microbiological quality. The above three bean flour types were used, and three baking methods were also compared. The baking processes were (1) 40 min at 120°C followed by 10 min at 100°C, (2) 40 min at 125°C and (3) 40 min at 105°C followed by 10 min at 120°C. Additionally, the proximate, total energy, organoleptic, and total bacterial counts were evaluated. The results showed that all banana bars can be classified as high-energy foods based on protein, fat, carbohydrate, and total energy. The organoleptic properties using different baking methods were not significantly different, and the highest score was found in the banana bar added with mung bean flour. In addition, the total bacterial count all products did not exceed the standard.